Equality in Education and Culture in Surkhandarya During the Years of Independence (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, life itself has shown that Uzbekistan, as an independent state, cannot mobilize the people to comprehensively strengthen its independence without a process of spiritual renewal in socio-political life. Therefore, from the very first days of independence, the republic's leadership took the necessary measures in this regard. In this regard, the President emphasized the need to give equal rights to all in the free choice of general secondary education, vocational training, and appropriate special training, as well as to develop and implement the New Democratic Concept.